Peri-urbanisation in Surakarta City and Economic Transformation in the Fast-Growing Region of Sukoharjo Regency - Wisnu Pradoto; Budi Setiyono; Hadi Wahyono; Mack Joong Choi (Forum Geografi)
The massive development of Surakarta City, a city with a strategic location, has caused a butterfly effect on its surrounding area. This research explores the economic transformation of Sukoharjo’s peri-urban, specifically in five districts, namely Mojolaban, Gatak, Grogol, Kartasura, and Baki, as the area adjacent to Surakarta City. A quantitative approach is employed with descriptive quantitative analysis techniques and scoring analysis. Primary data collection is based on the results of stakeholder’s interviews and field observations and secondary data gathered from government documents and literature review. The study results show that in the period 2000 – 2020, there has been economic transformation in Sukoharjo’s peri-urban area, especially the changes from rural to urban characteristics. The transformation can be indicated by the changes in population, livelihoods, agricultural land use, regional investment, and the number of emerging small and medium industries (SMIs) in each peri-urban region in the northern part of Sukoharjo. This research contributes a perspective on the unique characteristics of the diverse economic transformation driven by different patterns of land-use changes. It recommends that policymakers foster the roles of peri-urban areas in creating mutual development and sustainable urbanisation.